2009
DOI: 10.1111/j.1460-9592.2009.03140.x
|View full text |Cite
|
Sign up to set email alerts
|

How do pediatric anesthesiologists define intraoperative hypotension?

Abstract: There is great variability in the BP parameters used and the threshold used for defining and treating IOH among pediatric anesthesiologists. The majority of respondents considered a 20-30% reduction from baseline in SBP as indicative of significant hypotension. Lack of a consensus definition for a common clinical condition like IOH could have implications for patient care as well as future clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 21 publications
4
88
0
Order By: Relevance
“…Children who undergo general anaesthesia are not in their "normal" state of health, and intraoperative BP is most commonly recorded by the oscillometric method. 1,14 Recent studies have suggested that these values are inappropriate in critically ill or injured children. The other question is whether or not SBP, DBP or MAP should be considered.…”
Section: Hypotensionmentioning
confidence: 99%
See 3 more Smart Citations
“…Children who undergo general anaesthesia are not in their "normal" state of health, and intraoperative BP is most commonly recorded by the oscillometric method. 1,14 Recent studies have suggested that these values are inappropriate in critically ill or injured children. The other question is whether or not SBP, DBP or MAP should be considered.…”
Section: Hypotensionmentioning
confidence: 99%
“…1,3 Unfortunately, most information on paediatric BP measurement is obtained via extrapolations from adult data.…”
Section: General Issues In Blood Pressure Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The adult patients with secondary events had a higher American Society of Anesthesiologists (ASA) classifi cation and a lower baseline blood pressure, however. Other studies in the adult population have investigated preinduction treatments to prevent hypotension during propofol induction, including the use of isotonic fl uids, 17,18 Hetastarch, 19 ephedrine, 12,20,21 phenylephrine, 22 dopamine, dobu tamine, 20 ketamine, [23][24][25] and calcium chloride. 26 However, little research has been conducted specifi cally to determine whether there is a signifi cant risk to the pediatric patient during propofolinduced hypotension or whether there is an effective method to prevent the reduction in blood pressure associated with propofol induction in this patient population.…”
mentioning
confidence: 99%